Improved Mathematical Model for a Single-Ground Arcing Fault in Medium Voltage Distribution Networks - Jiaquan Ran; Qing Yang; Lewei He; Hongwen Liu; Tong Zhou; Siyu Wei (CSEE Journal of Power and Energy Systems)
Medium voltage distribution networks usually suffer from single-ground arcing fault, especially high impedance arcing fault. Moreover, induced intermittent arcing faults can severely endanger the reliability and safety of power systems. The arc model is important for high impedance arcing fault suppression and detection to effectively eliminate the single-ground arcing fault. This paper proposes an improved arc model, which is concise and explicit, based on a single-ground arcing fault conducted on a 10 kV experimental platform under different fault conditions. Characteristic parameters of single-ground arcing faults are obtained based on test results. Furthermore, characteristic parameters under different fault conditions of the improved arc model are presented. Finally, verification of the improved arc model is supported by PSCAD-EMTDC. Comparisons of the proposed arc model between three typical black-box arc models indicate that the proposed model has better performance and higher accuracy than that of the three typical arc models as fault resistance is in a range of 0.1 kΩ to 2.4 kΩ. Thus, its accuracy is acceptable and it is helpful to the simulation and suppression of arc fault overvoltage.